PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING START WITH A QUESTION (LSQ) TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII SMP NEGERI 16 SIJUNJUNG - Saputra Can, Yandris; Haryono, Yulia; Pratiwi, Merina (Pendidikan Matematika, 2014)
AbstractThe research was basic on Â the teacher as a center of learning process. The students had low motivated to ask the questions and gave their reason to the materials.The goal of this research was to determine whether students comprehension of mathematical concepts with the application by using active learning strategies LSQ was better than comprehension mathematical concepts by applying Conventional Teaching of second year students at SMPN 16 Sijunjung. In this research, the researcher used experimental method. The population of this research was the second year students of SMPN 16 Sijunjung. It was chosen by using random sampling technique, the experimental class was VIII2 students and the control class was VIII1 students. The instrument of the research was the final test with indicator of comprehension mathematical concepts in the form of essay with a 0.93 reliability test. The data analysis technique used is t-test. The result of this research processed with t-test was obtained tcount = 4.28 and Â ttable = 1.677 It can be concluded that the students comprehension of mathematical concepts by using active learning strategies LSQ type was better than students comprehension of mathematical concepts by using conventional learning second grade students of SMPN 16 Sijunjung.Â